DINAMIKA BENTUK-BENTUK SAPAAN SEBAGAI REFLEKSI SIKAP BERBAHASA MASYARAKAT INDONESIA - Ridha Mashudi Wibowo; Agustin Retnaningsih (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
Greetings are one of the tangible proofs of human communications. One greets someone else because of the need to communicate. In this communication, the relationship between the two people communicating influences the choice of greeting forms. The selection of a greeting is assumed to be closely related to the language attitudes and perspectives of the speaker in positioning himself against the hearer. During its development, the use of greetings has shown a quite interesting dynamics. This comprises the development of greeting use, shift of greeting reference, and changes in the acts of greeting. This paper aims to describe the term of addressing used by the society, analiyzing manner and logic structure of the term of addressing, also the actualization and the dynamics of the usage of the term of addressing. Furthermore, to obtain varied data the author determines a population consisting of a number of groups, especially university students. This is with the assumption that in addition to their age level where they are highly productive in using greetings, it is also possible that they have example forms of greetings and acts of greeting. Using speech act theory in sociolinguistics approach data was achieved with observation method in questioner and cards of data. The result of classification was analized with introspection, comparation, and equal-referential method which is formed in formal and informal description. From a number of semi-closed questionnaires listing questions about attitudes and selections of greeting the author obtains some results. These are a mapping of common greeting forms used by people in general, the background of common greeting forms used by people, and the actualization as well as dynamics of the use of greeting forms in Indonesian speech society.